The Effect Of People's Bussines Credit (KUR) PT. Papua Regional Development Bank Sentani BranchToward Micro Small And Medium Enterprises (MSMEs) In Jayapura District - mugiati, mugiati (AIBPM Publisher, 2024)
The purpose of this study was to determine the effect of People's Business Credit assistance on MSMES and to determine the increase in income for MSMES. This type of research is a quantitative research. The number of samples is 32 MSMES that take KUR at Bank Papua Sentani Branch. The analytical tools used in this study are data quality tests and simple regression analysis. From the linear regression function above, it can be explained that the Constant Value (a) has a positive value of 15.039 and the regression coefficient value for the People's Business Credit variable has a positive value of 0.606. Obtained t table of 2.04227. And t count 3.054 > 2.04227 t table based on the independent variable People's Business Credit has a positive effect on the dependent variable MSMES income. Judging from the significance of 0.005 it is <0.05 for the People's Business Credit variable. Based on this significant value, it can be said that the independent variable People's Business Credit has a positive effect on the dependent variable MSMES income. Based on the results of the research that has been done, it can be concluded that the People's Business Credit obtained from the Sentani Branch of Bank Papua is very influential on the income of MSMES in Jayapura Regency. And the income of MSMES in Jayapura Regency has increased and can develop their businesses after using People's Business Credit at PT. Papua Regional Development Bank Sentani Branch